PENGARUH TEKANAN ANGGARAN WAKTU, KOMPLEKSITAS TUGAS, KOMPETENSI DAN PROFESIONALISME TERHADAP KINERJA AUDITOR - Reyhan Jordy Daniro; Nur Asni Gani; Andry Priharta (Taksasila Edukasi Insani, 2023)
This study aims to analyze the effect of time budget pressure, task complexity, competence and professionalism on auditor performance. Conducted with a quantitative approach using primary data in the form of questionnaires with auditor respondents in South Jakarta. Since population size cannot be determined, convenience sampling techniques are used. Analysis using multiple linear regression with SPSS Version 25 application device. The results showed that time budget pressure had a significant positive effect on auditor performance, while task complexity, competence and professionalism did not affect auditor performance. Simultaneously, time budget pressures, task complexity, competence, and professionalism have a significant influence on auditor performance.Keywords: Time Budget Pressure, Task Complexity, Competence, Professionalism, Auditor Performance